Inflammasomes as the molecular hub of cardiovascular-metabolic-immune comorbidity networks - Qian, Xingyu; Sun, Jian; Li, Fei; Xu, Li; Hu, Xingjian; Dong, Nianguo; Li, Guangzhou (Frontiers in Immunology, 2025)
Cardiovascular, metabolic, and immune disorders intersect through inflammasome signaling, motivating the development of a unified framework for cardiovascular risk across obesity, diabetes, infection, and autoimmunity. We first outline inflammasome architecture and activation, highlighting cryo-EM evidence that NEK7 licenses NLRP3 assembly, the coupling of priming to ion-flux and oligomerization, and cross-talk with the non-canonical caspase-4/5/11 pathway that feeds forward into IL-1β/IL-18 maturation and pyroptosis. In metabolic disease, lipotoxicity, mitochondrial ROS, oxidized lipids, and crystalline cholesterol converge on NLRP3 across adipose, myeloid, and vascular compartments, driving endothelial dysfunction, plaque growth, and adverse cardiac remodeling. Immune system diseases further amplify cardiovascular injury: population-level data link autoimmunity to heightened CVD risk, while AIM2- and NLRP3-dependent axes accelerate atherogenesis and destabilize plaques, particularly in clonal hematopoiesis and after acute infectious or ischemic insults. Translationally, anti-inflammatory trials validate this biology—IL-1β blockade lowered recurrent events in CANTOS, and low-dose colchicine reduced events in chronic coronary disease—yet heterogeneity of benefit and safety signals underscores the need for precise patient selection and timing. We propose a path forward that mirrors disease chronology: dampen priming, selectively inhibit assembly, and modulate effectors (IL-1 pathway or pyroptosis). Collectively, this review integrates mechanism and medicine to position inflammasomes as actionable hubs linking metabolic dysfunction, immune dysregulation, and cardiovascular disease, and charts priorities for precise, durable prevention and therapy.